Scientific Communication and Student Interest in Biology Learning through Pictorial Riddle Method - Lailatun Nisfiyah; Ratih Oktatira; Riza Indriyani; Reti Purwasi; Tasya Alya Permata; Indah Juwita Sari (Indonesian Journal of Biology Education, 2024)
Currently, the main challenge in education is to increase student engagement in science learning. Scientific communication skills are critical skills students need. The use of Pictorial Riddle method is a technique, way or effort made in learning to inform scientific facts for students through images, for example presented in the form of posters, pictures on the blackboard, or projections contained in object transparencies. This study aims to explore how the use of Pictorial Riddle learning method can improve students' scientific communication skills and at the same time arouse their interest in science learning. The method used in this research is a case study, using a sample of 57 students of class XI MIPA selected by random sampling technique. The results showed that the Pictorial Riddle learning method has a good effect on students' interest in science learning where students get learning equipped with pictures on the learner worksheet to be analyzed by students. The Pictorial Riddle approach opens space for student creativity, increases active participation, and strengthens understanding of scientific concepts. This can be the basis for innovative learning approaches, namely with a group learning system to develop scientific communication skills and increase student interest in science learning